SCENARIO-BASED SWMM MODELING OF LOW IMPACT DEVELOPMENT FOR RESILIENT URBAN DRAINAGE - Sevia, Riska Ayu; Silvia, Cut Suciatina; Hasdanita, Fitry (Center for Environmental Studies, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
Urban drainage systems in Meulaboh City face increasing challenges due to rapid urbanization, extensive impervious surfaces, and inadequate stormwater management. This study evaluated the performance of the existing drainage system and assessed the effectiveness of Low Impact Development (LID) practices using the EPA SWMM 5.2.4 model. Hydrological and hydraulic simulations were conducted under existing conditions and three LID scenarios: rain barrels, permeable pavement, and vegetative swales. Results showed that drainage channels S30, S53, S63, S71, and S107 experienced overflow due to insufficient channel capacity, sedimentation, and limited infiltration areas. LID implementation reduced runoff volume and peak discharge compared to existing conditions. Rain barrels achieved the highest runoff reduction (11–16%), followed by permeable pavement (up to 12%), while vegetative swales showed limited effectiveness (<1%). Although overflow was not completely eliminated, the findings demonstrate that LID practices can significantly improve urban drainage performance and provide a sustainable approach to stormwater management in Meulaboh City.